2014
DOI: 10.3389/fncel.2014.00219
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the extracellular matrix on endogenous and transplanted stem cells after brain damage

Abstract: The limited regeneration capacity of the adult central nervous system (CNS) requires strategies to improve recovery of patients. In this context, the interaction of endogenous as well as transplanted stem cells with their environment is crucial. An understanding of the molecular mechanisms could help to improve regeneration by targeted manipulation. In the course of reactive gliosis, astrocytes upregulate Glial fibrillary acidic protein (GFAP) and start, in many cases, to proliferate. Beside GFAP, subpopulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 324 publications
(372 reference statements)
1
43
0
Order By: Relevance
“…Histological inspection of the brains revealed that DsRed was easily observable without immunocytochemistry, whereas eGFP required anti-GFP immunocytochemistry for visualization (data not shown; there were also no overt tumors). Because of this pattern, we could use an anti-nestin primary antibody conjugated to a green fluorophore (results are shown as a white channel) to detect the grafts in all rats, as this coreacted with both infiltrating endogenous nestin-positive reactive cells around the graft 24,25 and (to a lesser extent) the transplanted 6B6D-NPCs. Conversely, an anti-DsRed antibody was used to further amplify and analyze the MFP-inducible transgene expression of our cells in vivo (Figures 6–8).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Histological inspection of the brains revealed that DsRed was easily observable without immunocytochemistry, whereas eGFP required anti-GFP immunocytochemistry for visualization (data not shown; there were also no overt tumors). Because of this pattern, we could use an anti-nestin primary antibody conjugated to a green fluorophore (results are shown as a white channel) to detect the grafts in all rats, as this coreacted with both infiltrating endogenous nestin-positive reactive cells around the graft 24,25 and (to a lesser extent) the transplanted 6B6D-NPCs. Conversely, an anti-DsRed antibody was used to further amplify and analyze the MFP-inducible transgene expression of our cells in vivo (Figures 6–8).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, CellProfiler 26 was used to quantitate the number of DsRed-positive mNPCs in regions with a large cluster of endogenous nestin-positive reactive cells 24,25 (Supplementary Figure S2). By quantifying the nestin and DsRed signals adjacent to the transplant site, this analysis allowed for single-cell identification as well as eliminating potential concerns associated with autofluorescent material within the graft cores.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, the enzymatic removal of CSPGs by chondroitinase ABC at the damage site leads to significant improvements in the connections reestablishment, and more important, to functional recovery of motor functions [20,21,53,90,91]. One possible mechanism for it could be facilitation of oligodendrocytic migration, and, therefore, promoting remyelination [5,55,92,93]. Moreover this positive effect of chondroitinase ABC treatment remains sufficient to promote motor recovery on day 2, 4 and 7 following injury [20].…”
Section: а Bmentioning
confidence: 99%